Optimization of Distribution Network Inspection Using Drones to Improve Maintenance Effectiveness - Nanda, Muhammad Yoga Prima (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The maintenance of Medium Voltage Overhead Distribution Lines (SUTM) requires effective inspection methods to ensure the reliability of power supply. Conventional inspection methods have limitations in comprehensively detecting damage and are less efficient in terms of time, cost, and worker safety. The use of drones as an alternative technology offers a faster, more accurate solution capable of reaching difficult areas, thereby improving the effectiveness of distribution network maintenance. This study aims to optimize the use of drones in inspecting SUTM distribution networks by comparing the effectiveness, time efficiency, and operational costs between conventional methods and drone-based inspections. The results of the study indicate that the average inspection time was reduced from 66.45 minutes (conventional) to 21.20 minutes (drone), resulting in a 68.1% improvement in time efficiency. The average operational cost decreased from Rp 648,220 to Rp 298,380, equivalent to a 54% cost saving. Furthermore, the number of faults detected increased from 2.58 to 6.70, representing a 159.7% enhancement in detection effectiveness. Therefore, the implementation of drones in distribution network inspections is a strategic step to support a more reliable and modern maintenance system.